Multimodal input in computer-assisted simultaneous interpreting: Effects on interpreting quality, cognitive load, and attention dynamics - Peng, Xuejiao; Wang, Xiangling; Chen, Guangjiao (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2025)
Computer-assisted simultaneous interpreting (CASI) is increasingly exposing interpreters to multimodal digital environments by means of added visual input. Yet little is known about how multimodal text and speaker inputs affect overall interpreting quality, cognitive load, and attention dynamics. Drawing on analyses of quality assessment, self-reported questionnaires, and eye-tracking data, this study compared CASI with conventional SI regarding the effects on overall interpreting quality, cognitive load, and attention dynamics. In it, 30 student interpreters performed simultaneous interpreting (SI) from English to Chinese across four input conditions: audio-only, audio–video, audio–text, and audio–video–text. The results indicate that the visual input provided by CASI tools significantly improved their interpreting quality and reduced their cognitive load; moreover, the audio–video–text CASI condition yielded the highest interpreting quality and a relatively low cognitive load. In addition, the student interpreters strategically adjusted their attention across different visual input conditions. When audio, video, and text inputs were available concurrently, they prioritized textual input over both auditory cues and speaker video and demonstrated distinct patterns of strategic coordination. In this article, the theoretical, practical, and pedagogical implications of these findings are discussed.